2006
DOI: 10.1108/01409170610708998
|View full text |Cite
|
Sign up to set email alerts
|

Successful women of the Americas: the same or different?

Abstract: Purpose -The intent of this cross-national research is to study the personal and cultural characteristics of successful professional women. High-achieving women may share certain personal characteristics, beliefs, and experiences, regardless of the countries in which they live. However, every individual is socialized within a particular national culture, and may be expected to share certain values and expectations with other members of that culture. Design/methodology/approach -Over 1,100 professionally ''succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…However, our research demonstrates this does not necessarily mean similar (certainly not equivalent) self-efficacy patterns based on national level comparisons for Canada and the United States. The findings might also indicate that while national culture may be relevant, individual nuances are likely more significant; something that supports other work on patterns of self-efficacy in the Americas (Duffy et al, 2006). This observation is particularly important for organizations seeking to hire the most self-efficacious employees from international pools of candidates.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…However, our research demonstrates this does not necessarily mean similar (certainly not equivalent) self-efficacy patterns based on national level comparisons for Canada and the United States. The findings might also indicate that while national culture may be relevant, individual nuances are likely more significant; something that supports other work on patterns of self-efficacy in the Americas (Duffy et al, 2006). This observation is particularly important for organizations seeking to hire the most self-efficacious employees from international pools of candidates.…”
Section: Discussionmentioning
confidence: 59%
“…Our research also suggests that as female employees gain work and management experience, their levels of self-efficacy will be positively impacted. It is suggested that such personal developments will directly impact career satisfaction and career success (Duffy et al, 2006;Punnett et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to sound economic and trade policies, higher rates of literacy, and changing attitudes toward women in management, women in South American countries (e.g. Chile) seem to have somewhat overcome institutional and social barriers to achieve a higher level of career success (Duffy et al, 2006;Punnett et al, 2007). In China, which has the lowest GDP as compared to the USA and Chile, women are not found frequently in managerial roles (Frank, 2001), and women are seen as having little or no place being in the male-dominated working world (Liu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%